(untitled) (BEOIBERÍSTICA - Journal of Iberian, Latin American and Comparative Studies (ISSN: 2560-4163 Online), 2018)
The objective of this article is to study the impact of the variable “gender” in the available lexicon of 350 Moroccan students who learn Spanish as a foreign language at the Faculty of Letters and Human Sciences of Agadir (Morocco) and who show a great interest in teaching / learning this language. After making a brief tour through the history of lexical availability, we come up with the analysis of the variable that concerns us in the whole of the sample to follow then with its correlation with the “academic course”. The quantitative analysis of the results obtained allows us to offer revealing data about the marked association between lexical availability and “gender”. Key words: lexical availability, Spanish as a foreign language, Moroccan students, lexical productivity, lexical competence.